ABT-737 overcomes resistance to immunotoxin-mediated apoptosis and enhances the delivery of Pseudomonas Exotoxin-based proteins to the cell cytosol - Traini, Roberta (2010)
Pseudomonas exotoxin (PE)-based immunotoxins (antibody-toxin fusion proteins) have achieved frequent complete remissions in patients with hairy cell leukemia but far fewer objective responses in other cancers. To address possible mechanisms of resistance, we investigated immunotoxin activity in a model system using the colon cancer cell line, DLD1. Despite causing complete inhibition of protein synthesis, there was no evidence that an immunotoxin targeted to the transferrin receptor caused apoptosis in these cells. To address a possible protective role of prosurvival Bcl-2 proteins, the BH3-only mimetic, ABT-737, was tested alone or in combination with immunotoxins. Neither the immunotoxin nor ABT-737 alone activated caspase 3, while the combination exhibited substantial activation. In other epithelial cell lines, ABT-737 enhanced the cytoxicity of PE-related immunotoxins by as much as 20-fold, but did not enhance diphtheria toxin or cycloheximide. Because PE translocates to the cytosol via the endoplasmic reticulum (ER) and the other toxins do not, ABT-737-mediated effects on the ER were investigated. ABT-737 treatment stimulated increased levels of ER stress response factor, ATF4. Because of its activity in the ER, ABT-737 may be particularly well suited for enhancing the activity of immunotoxins that translocate from the ER to the cell cytosol.